NIEMIECKA USTAWA O SPÓŁCE Z OGRANICZONĄ ODPOWIEDZIALNOŚCIĄ – NAJNOWSZE ZMIANY - Gawrysiak-Zabłocka, Aleksandra (Zeszyty Prawnicze, 2017)
The German Private Limited Liability Act – Recent Changes Summary The Gesellschaft mit beschränkter Haftung (GmbH – Private Limited Company) is the most popular organizational form for businesses in Germany – numbering almost one million entities. Nevertheless, few changes had been made since its inception in the late 19th century, leading to complex case law. Moreover, in the famous Centros case the ECJ decided that a businessperson may legally incorporate his or her business anywhere in the European Union, even if this happens for the sole reason of avoiding a stricter national corporate regime. As a result many Germans decided to establish company in U.K. because Ltd. legal regime was by no means more transparent and accessible than the GmbH legal regime (no requirement of minimum share capital). In such a situation, after long discussions, German parliament adopted Gesetz zur Modernisierung des GmbH-Rechts und zur Bekämpfung von Missbräuchen (MoMiG – Law for the Modernisation of the German Limited Liability Company Law and the Prevention of Misuse) which came into force on the 1 November 2008. In the article some of the most important features of the new GmbH-Recht are analyzed. Changes in German law could be an important inspiration for Polish legislator since the discussion on how to make Polish spółka z ograniczoną odpowiedzialnością more competitive and how to prevent abuse of company law is currently underway in our country.